Hoplothrips species recorded from China (Thysanoptera, Phlaeothripidae), with one new species from Yunnan - Mound, Laurence A.; Wang, Jun (Zootaxa, 2020)
The genus Hoplothrips is the third most species-rich in the subfamily Phlaeothripinae (Mound et al. 2020), and currently comprises 131 species (ThripsWiki 2020). Most of these live on dead branches of woody angiosperm trees and are presumed to feed on fungal hyphae or their liquid breakdown products (Kobro & Rafoss 2006). Many species in this genus exhibit considerable sexual dimorphism, also considerable polyphenism associated with variation in body size. As a result of this variation in body structure, species identification in this genus is often difficult (Mound & Walker 1986; Mound 2017; Mound et al. 2018).